Economic damage caused by the cotton stem borer in southern Brazil - dos Santos, Walter Jorge; Gutierrez, Andrew Paul; Pizzamiglio, Marina Angela (Pesquisa Agropecuaria Brasileira, 2014)
Cotton stem borer, Eudnobothurs brasiliensis damage showed a graded distribution from Lhe margin of the field to the middle. Infestation was considerably higher in the border rows than in the center of the field. The study documented the behavior of this pest during the period when it migrates from overwintering sites around the field to cotton. The results confirm former observations that the levels of infestation are higher near humid overwintering areas with permanent vegetation, Early planted blocks of cotton had the highest rates of infestation, often reaching 70% of plant mortality. In later plantings a 20% reduction in plant mortality was observed every time planting was delayed for ten days. The data suggest that this pest may be controlled with insecticide applications in border rows. This procedure would eliminate the need of chemical treatments which are environmentally unsound. The data also suggest that planting densities of nine to ten plants per m would help to reduce the impact of this pest on cotton yield. The relationship between yield loss and plant mortality was assessed and the economic damage estimated.